2016
DOI: 10.25077/jpi.18.1.44-52.2016
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Genetik Gen Hormon Pertumbuhan (GH|MboII) pada Itik Sikumbang Janti Menggunakan Penciri PCR-RFLP

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui keragaman gen hormon pertumbuhan (GH) dengan enzim MboII pada itik Sikumbang Janti dengan menggunakan penciri PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism). Penelitian ini menggunakan sebanyak 50 sampel darah itik Sikumbang Janti. Sampel darah itik Sikumbang Janti diambil melalui vena achilaris sebanyak ± 1 ml. DNA sampel darah diisolasi menggunakan protocol Genomik DNA Purification Kit (Promega). DNA total diamplifikasi menggunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
0
7
1
1
Order By: Relevance
“…This study's primary length of the GH gene amplified was 879 base pairs (bp). The outcomes of this observe are not same from those of [23], who stated that the amplified primary length of the GH gene was 801 bp. This is due to the use of different primers.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This study's primary length of the GH gene amplified was 879 base pairs (bp). The outcomes of this observe are not same from those of [23], who stated that the amplified primary length of the GH gene was 801 bp. This is due to the use of different primers.…”
Section: Discussioncontrasting
confidence: 59%
“…Mutation occurs around the cutting position. The outcomes of this observe are not a lot exclusive from the research of [23], who stated that diversity of GH genes in exon 1, which was cut with the MboII enzyme, showed that the GH gene of Sikumbang Janti ducks was polymorphic characterized by the appearance of genotypes (+/+), (+/-), and (-/-) and two alleles + and -. Sutopo et al [26] stated that the population of Demak and Pekalongan ducks found two alleles on the GH gene, (+) and (-), which formed homozygous characters (+/+) and (-/-) and heterozygous (+/) characters.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…DNA extraction aims to obtain DNA with excellent quality, which has high purity. DNA purification is a process to separate DNA from cell lysates (proteins, carbohydrates, lipids) and other contaminants (Hernandez et al, 2006;Nova et al, 2016). Bangkok chicken DNA extraction results from 50 blood samples were electrophoresed using 1.5% Agarose, which were visualized using UV light through Gel Doc presented in Figure 3.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Salah satu gen kandidat yang berperan dalam peforma yang bersifat ekonomis yaitu Gen Growth hormone Receptor atau GHR (Yurnalis dan Sarbaini 2014;Nova et al 2016). GHR diduga mempengaruhi keragaman itik Sikumbang Janti.…”
unclassified